Analisis Peran Paralegal Dalam Hak Memberikan Pelayanan Bantuan Hukum Bagi Masyarakat Yang Terjerat Kasus Pinjaman Online - Ramadhan, Yogha Aditya; Setiawan, Ichwan (PT Elaborium Elevasi Indonesia, 2025)
This research is based on the phenomenon of the rapid growth of online lending in Indonesia, which is often accompanied by predatory lending practices, causing legal problems for the community, especially vulnerable groups. The main problem formulation is how the role of paralegals in providing legal aid services, as well as the extent to which the effectiveness of legal aid provided. The research method used is qualitative with a case study approach. Data was collected through direct observation with paralegals who are actively providing legal assistance to victims of online lending, as well as with communities who have received legal assistance from paralegals. The findings show that paralegals play an important role in improving access to justice for victims of online lending. These roles include providing legal information and education, legal advice, assistance with negotiation and mediation, and assistance with reporting to authorities. The effectiveness of paralegal legal assistance is influenced by paralegal competence, support from law enforcement officials, access to information, and collaboration with legal aid institutions. The study concludes that paralegals have great potential to make a significant contribution to achieving more equitable access to justice for the community.